Evaluasi Konsep Bangunan Hijau pada Bangunan Rusunawa Pesakih di Jakarta Barat - Maudy Latuconsina; Andika Citraningrum (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Global warming is getting worse also accompanied by climate change makes human habit have to change too. Eco-friendly lifestyles are being implemented in many countries, including Indonesia. This is evidenced by the emergence of eco-friendly buildings (green buildings). In DKI Jakarta still not optimal in implementation of the Governor Regulation number 38. To solve the problem, the government undertakes a commitment to make DKI Jakarta as the Center of Excellence in Indonesia in 2030. The study assesses vertical dwelling in the super blocks of Pesakih, Rusunawa Pesakih to know the concept green buildings that implemented according to GBCI standard. The standard used is Greenship Existing Building version 1.1 with six categories and each criterion in it. The method used descriptive qualitative. As the result of the existing evaluation, the Rusunawa Pesakih earned 47 points which categorized SILVER rating. Then from the results of existing evaluation made recommendations. Recommendations are divided into two: architectural and non-architectural recommendations. The total points after the recommendation are 80 points and get the PLATINUM rating.